Walking, trip purpose, and exposure to multiple environments: A case study of older adults in Luxembourg. (June 2019) - Perchoux, Camille; Brondeel, Ruben; Wasfi, Rania; Klein, Olivier; Caruso, Geoffrey; Vallée, Julie; Klein, Sylvain; Thierry, Benoit; Dijst, Martin; Chaix, Basile; Kestens, Yan; Gerber, Philippe
Abstract: Purpose: Understanding the geographical and environmental triggers for active transport among older adults is crucial to promote healthy and independent lifestyles. While transportation research has long considered trip purpose as a major determinant of transport mode choices, "place and health" research has paid little attention to it, and even less in connection with environmental determinants. To avoid an oversimplification of how neighborhood built environments influence utilitarian walking, it is critical to account simultaneously for trip purposes, the locations of visited places, and the related exposure to surrounding environments. Methods: Based on a cohort of 471 older adults in Luxembourg, this study examines the influence of trip purposes on utilitarian walking, and the potential interaction effects with characteristics of multiple geographic environments and distance to the place of residence. Information related to demographics, health status, and regularly visited destinations was collected in 2015 and 2016. Associations between trip purpose, environment, distance, and walking were analyzed using multilevel logistic regressions, accounting for demographics, neighborhood self-selection, and health status. Results: After accounting for environmental attributes, distance, and confounding factors, trip purpose remained a strong correlate of walking among older adults. Associations between distance and walking strongly differed by trip purpose (Wald Chi 2 test p < 0.001). Access to amenities, public transport stops, and street connectivity were associated with walking, although no interaction with trip purpose was observed. Conclusion: Trip purposes based on free-time activities–including visits to family and friends, and restaurants and cafés–seem to be less influenced by the barrier effect of distance on walking. While place and health studies increasingly address both the "where" and "when" of travel behaviors, the current study additionally stresses the importance of the trip purpose to emphasize "why" and "for what" people walk. Highlights: Trip purpose is a key correlate of utilitarian walking among older adults. Connectivity, access to public transport and amenities are associated with walking. Environmental influence on walking does not vary by trip purpose. Trip purpose modifies the association between distance and walking.